ChemInform Abstract: Heterometallic Cube‐Type Molecular Nitrides. Issue 23 (May 2016) - Mena, Miguel; Perez‐Redondo, Adrian; Yelamos, Carlos
Abstract: Review: [emphasis on nitrido complexes with cuboidal [MTi3 N4 ] cores; 96 refs.].